About interrelations between working conditions of workers of city-forming enterprises and the degree of their adaptation to the characteristic mode of labor and rest - V. V. Kriulina; G. Yu. Avdienko; O. S. Ivanov (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
Introduction. Prevention of adaptation diseases, particularly distress syndrome, is an urgent task in preventive and industrial medicine. The quality of life of employees is associated with their socio-psychological, psycho-physiological, and functional states. A prolonged state of distress can lead to a breakdown of the body's adaptive mechanisms and the development of chronic diseases. The aim of the study was to identify potentially feasible methods for the prevention of distress among workers in various professions. Materials and methods. A survey was conducted among 54 employees of a large industrial city-forming enterprise using developed questionnaires "Subjective assessment of working conditions" and assessment of the presence and severity of stress symptoms. The presence of symptoms of occupational stress was considered at the physiological, psychological, and social levels. Results. Using Spearman's nonparametric correlation method, relationships were established between the subjective assessment of working conditions by an employee, the severity of stress symptoms, and indicators of quality of life. Direct statistically significant associations were found between the conditions of work activity and physiological, social, and integral indicators of stress. An inverse correlation was found between role functioning due to emotional state and social signs of stress. Direct correlations were established between the "Mental Health" indicator (presence of depression and anxiety) and psychological signs of stress, as well as the integral stress indicator. The results demonstrate that the working environment and factors of the labor process have a significant impact on personnel, provoking the development of stress and a decrease in the quality of life. Conclusion. It seems relevant to continue applied scientific research aimed at developing elements of a promising system for predicting and early prevention of vegetative disorders (adaptation diseases) among employees of large industrial facilities. Such a system should be adapted to the existing structure of production processes and relationships at specific specialized city-forming enterprises.